Spinal Cord Herniation into a Pseudomeningocele—A Delayed Presentation following a Traumatic Cervical Root Avulsion Injury - Patel, Jay; Stewart, James; Biswas, Shubhabrata; Zaid, Sarsam (Indian Journal of Radiology and Imaging, 2023)
Background Spinal cord herniation into a traumatic pseudomeningocele is a rare clinical entity. We present the sixth known case and describe surgical management.Case Presentation A 44-year-old male presented with Brown-Sequard syndrome three decades after a cervical nerve root avulsion injury. Imaging revealed hemicord herniation into a C7/T1 pseudomeningocele in addition to extra-axial cord compression from further pseudomeningoceles. Significant clinical improvement was achieved following surgical repair. The radiological findings and technique for operative repair are described.Conclusion The case highlights this rare pathology and presentation, describes the surgical measures for repair of cord herniation, and provides evidence for the favorable outcome that can be achieved by surgical intervention.
Keywords: pseudomeningocele; herniation; spinal cord; trauma